PENGGUNAAN PUPUK KOMPOS DAN PUPUK MIKRO PADA PEMBIBITAN KELAPA SAWIT (Elaeis guineensis Jacq.) DI MEDIUM GAMBUT - Leny Husin; Gulat Medali Emas Manurung; M. Amrul Khoiri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The utilization of peat as a growing medium is oil palm breeding prospect of oil palm plantations that need to be studied, because the peat soil fertility is low, then the addition of compost and fertilizer micro as ameliorant material to improve soil fertility in peat. This study aims to determine the effect of the use of compost and fertilizer micro-dose combinations as well to get the best fertilizer in oil palm seedlings in peat medium .This study was performed experimentally using a completely randomized design experiments (CRD) with 2 factors and 3 replications. The first factor is the dose of compost fertilizer (K) which consists of 4 levels and the second factor is the dose of micro (M), which consists of 2 levels. The parameters measured were high accretion seeds (cm), increase the number of leaves (leaf), seed weevil added girth (cm), ratio feature roots and dry weight of seedlings (g). The data analysis results were significant statistical test followed by Duncan's test New Multiple Range Test (DNMRT) at the 5% level. The results showed that the best combination found in compost dose of 150g/ poly bag and fertilize rmicro4g/poly bag, but did not differ significantly with doses of50g/poly bag compost fertilizer micro poly bag and 4g/poly bag being able to show the highest results in the high gain parameter seeds, increase the number of leaves, seed we eviladded girth, crown root ratio and dry weight of  seedlings.   Keywords: Palm oil, compost, fertilizer micro, combination treatment